School freezes over! - Chabert, Jack; Ricks, Sam (New York, NY : Branches/Scholastic Inc., 2016)
A heavy snowstorm traps the students inside Eerie Elementary, a living, breathing monster brought to life by mad scientist, Orson Eerie--soon the school begins to freeze from the inside out, and Sam, Lucy and Antonio must find a way to get the heat back on before all the students freeze to death, while facing the truth that Orson Eerie is even more powerful and dangerous than they realized
Grades: 1-3
Grade: 2
Keywords: Elementary schools -- Juvenile fiction; Haunted schools -- Juvenile fiction; Blizzards -- Juvenile fiction; Best friends -- Juvenile fiction; Horror tales; Elementary schools -- Fiction; Schools -- Fiction; Haunted places -- Fiction; Blizzards -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Horror stories; Horror fiction; Fiction; Horror stories; Horror fiction; Horror fiction